Factors predicting clinical outcomes of endoscopic submucosal dissection in the rectum and sigmoid colon during the learning curve - Agapov, Mikhail; Dvoinikova, Ekaterina (Endoscopy International Open, 2014)
Background and study aims: Colorectal endoscopic submucosal dissection (ESD) is associated with significant technical difficulty, long procedure time, and increased risk of complications, especially perforation. This study aimed to determine the factors associated with clinical results of ESD during the learning curve.Patients and methods: In total, 44 patients with sessile and flat rectal and sigmoid colon lesions underwent ESD from November 2009 to September 2013. The procedure time, resection method, tumor size, location, gross morphology, presence of fibrosis, histologic findings, rates of en bloc and piecemeal resections and perforation were analyzed. The ESD procedure was classified as technically difficult in the case of procedure time > 120 minutes and/or piecemeal resection. The whole study time was divided into two periods: first period: resections 1 – 22, second period: resections 23 – 44.Results: En bloc and R0 resection have been achieved in 84.1 % of lesions. The mean procedure time was 119.95 ± 11.22 minutes (range 25 – 360 minutes). Perforation was seen in five cases (11.4 %). A larger tumor size was a risk factor for difficult ESD (P = 0.0001). A finding of fibrosis was a risk factor for piecemeal ESD (P = 0.0074), and perforation (P = 0.0012). There was a high direct positive correlation between tumor size and operation time (r = 0.83, P < 0.0001, 0.95 and 0.99 confidence interval for rho 0.71 – 0.904). There was no significant difference between the first and second period in terms of mean procedure time, en bloc resection or complication rate.Conclusion: A larger tumor size was associated with technically difficult ESD. Severe submucosal fibrosis was a risk factor for both piecemeal resection and perforation.